Peran Masyarakat Lokal dalam Usaha Pelestarian Naskah-Naskah Kuno Paseban - Yona Primadesi (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
This study aims to determine the role of local communities in conservation efforts of Paseban manuscripts. This research uses dominant less-dominant design, which combines quantitative and qualitative approaches in one study. The data were obtained from field observations, interviews, and library studies. The results are the conservation efforts undertaken on manuscripts in surau Paseban were limited to activities to save the script and clean manuscripts from dust and dirt. There were no special conservation activities on these texts, and the activities tended to damage the manuscript. The recommendation is the community is more responsive to the presence and the values of the manuscripts so that the joint conservation activities can be done optimally. In addition, special attention from the government for handling the manuscripts is needed. Key words: conservative manuscripts, surau Paseban, conservation efforts